Alcohol Dehydrogenase‐1B Genotype (rs1229984) is a Strong Determinant of the Relationship Between Body Weight and Alcohol Intake in Japanese Alcoholic Men. (15th February 2013) - Yokoyama, Akira; Yokoyama, Tetsuji; Matsui, Toshifumi; Mizukami, Takeshi; Matsushita, Sachio; Higuchi, Susumu; Maruyama, Katsuya
<x xml:space="preserve">Abstract</x> Background The calories in alcoholic beverages consumed by alcoholics are a major energy source and a strong modifier of their body weight. Genetic polymorphisms of alcohol dehydrogenase‐1B (ADH1B) and aldehyde dehydrogenase‐2 (ALDH2) affect susceptibility to alcoholism and may affect body weight via gene‐associated differences in fuel utilization in alcoholics. Methods We evaluated associations between ADH1B/ALDH2 genotypes and the body weight and body mass index (BMI) of 1, 301 Japanese alcoholic men at the time of their first visit to an addiction center. Results Median (25th to 75th) caloric intake in the form of alcoholic beverages was 864 (588 to 1, 176) kcal/d. Age‐adjusted caloric intake did not differ according to ADH1B/ALDH2 genotypes. The body weight and BMI values showed that the ADH1B*2/*2 and *1/*2 carriers (n = 939) were significantly leaner than the ADH1B*1/*1 carriers (n = 362) irrespective of age, drinking, smoking, and dietary habits. The age‐adjusted body weight values of the ADH1B*2/*2, ADH1B*1/*2, and ADH1B*1/*1 carriers were 58.4 ± 0.4, 58.7 ± 0.5, and 63.6 ± 0.5 kg, respectively (ADH1B*2 vs. ADH1B*1/*1 carriers, p < 0.0001), and the corresponding BMI values were 21.0 ± 0.1, 21.0 ± 0.1, and 22.9 ± 0.2 kg/m2, respectively (ADH1B*2 vs. ADH1B*1/*1 carriers, p < 0.0001). No effects of inactive ALDH2 on body weight or BMI were observed. A multivariate analysis showed that BMI decreased by 0.35 per 10‐year increase in age, by 1.73 in the presence of the ADH1B*2 allele, by 1.55 when the preferred beverage was whiskey, and by 0.19 per +10 cigarettes/d and that it increased by 0.10 per +22 g ethanol (EtOH)/d and by 0.41 per increase in category of frequency of milk intake (every day, occasionally, rarely, and never). The increase in BMI as alcohol consumption increased was significantly smaller in the ADH1B*2 group than in the ADH1B*1/*1 group (p = 0.002). Conclusions ADH1B genotype was a strong determinant of body weight in the alcoholics. The more rapid EtOH elimination associated with the ADH1B*2 allele may result in less efficient utilization of EtOH as an energy source in alcoholics.